Study of Geometric Illusory Visual Perception – A New Perspective in the Functional Evaluation of Children With Strabismus - Rohr, Juliana Tessari Dias; Isaac, Cassiano Rodrigues; de Lima, Adriano de Almeida; Garcia, Ana; dos Santos, Procópio Miguel; Tavares, Maria Clotilde Henriques (Frontiers in Human Neuroscience, 2022)
Despite the various perceptual-motor deficits documented in strabismus, there is a paucity of studies evaluating visual illusions in patients with strabismus. The aim of this study was to examine how the illusionary perception occurs in children/adolescents (10-15 years old) with strabismus with referral for surgery to correct ocular deviations. A controlled cross-sectional study was carried out in which 45 subjects with strabismus and 62 healthy subjects aged 10-15 years were evaluated. The behavioral response to three geometric illusions (Vertical-Horizontal illusion, Müller-Lyer illusion (Bretano version) and Ponzo illusion) and respective neutral stimuli (non-illusory images) regarding the estimation of image size and response time were measured using the Method of Adjustment. To analyze the influence of secondary factors: type of ocular deviation (convergent, divergent or associated with vertical deviation); amount of eye deviation; presence of amblyopia and stereopsis, a one-way ANOVA was performed. Among the tested illusions, children with strabismus showed greater susceptibility (p=0.006) and response time (p=0.004) to Ponzo's illusory images. Children with strabismus and preserved stereopsis, on the other hand, showed similar susceptibility and response time to control group patients to the Ponzo illusion (p<0.005). Patients with amblyopia showed overcorrection in the estimate of non-illusory Ponzo images (p=0.046). Children with horizontal ocular deviation (esotropia or exotropia) associated with vertical deviation (hypertropia, DVD and/or alphabetical anisotropy) showed higher susceptibility to vertical adjustment images for the Müller-Lyer illusion (Brentano version) (p=0.017). Individuals with strabismus tended to overcorrect the length of the straight-line segment adjusted for non-illusory images when testing non-illusory images in the Müller-Lyer test (Brentano version) (p=0.009), as well as for the neutral images in the Vertical-Horizontal test (p=0.000). The findings indicated impairment in the perception of geometric illusions and neutral figures, especially for the Ponzo illusion test by children with strabismus. As the behavioral response to illusory images may indirectly reflect the visual and morphofunctional alterations present in these individuals, we suggest that the investigation of visual illusory perception can be used as a new research strategy in the field of investigating the visual function in strabismus.